Iran, Kazakhstan and China: The implementation of the program “one belt – one road” (Journal of Oriental Studies, 2019)
This article analyzes relations between China, Iran and Kazakhstan in the context of China’s new program and the removal of sanctions against Iran. Considered the economic and political aspects of the strengthening of China in the Middle East, found its features and the most important aspects of bilateral relations between Iran and China and China and the Republic of Kazakhstan. Also, were considered patterns of development and analyzed the objective socioeconomic situation in the context of the new Chinese initiative “One belt oneroad” and the formation of a new geopolitical situation after the removal of sanctions against Iran. This article analyzes the relations between three countries in the context of mutual synergy of the new economic policy of Iran, Kazakhstan and China. Analyzed the effectiveness of the current economic and trade relations and predicted new horizons of mutual beneficial relations. The article is based on the use of the interdisciplinary nature of the subject and on the works of Kazakhstan and foreign authors. Key words: program, regional cooperation, economy, diplomacy, foreign policy initiatives, the main actors.